Industrial Parks In Russia: Conceptual Development Of The Project - Sandler, Daniil Gennadyevich; Kuznetsov, Pavel Dmitriyevich (Economy of Regions, 2015)
The paper presents a theoretical framework of industrial parks effectiveness as an element of economic policy to accelerate economy development in regions or municipalities. The article studies how historically such instruments were used in modern Russia. The paper states the necessity of extensive development of the industrial park concept and how it affects the chances of project realization and potential economic effectiveness. The main parts and blocks that should be taken into account during concept preparations are highlighted, and proposals for their content are made.